Intracellular delivery of proteins by nanocarriers. (April 2017) - Ray, Moumita; Lee, Yi-Wei; Scaletti, Federica; Yu, Ruijin; Rotello, Vincent M
Intracellular delivery of proteins is potentially a game-changing approach for therapeutics. However, for most applications, the protein needs to access the cytosol to be effective. A wide variety of strategies have been developed for protein delivery, however access of delivered protein to the cytosol without acute cytotoxicity remains a critical issue. In this review we discuss recent trends in protein delivery using nanocarriers, focusing on the ability of these strategies to deliver protein into the cytosol.